2022
DOI: 10.1212/nxi.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

CNS Involvement in Chronic Inflammatory Demyelinating Polyneuropathy

Abstract: Background and ObjectivesChronic inflammatory demyelinating polyneuropathy (CIDP) is an autoimmune disease primarily affecting the peripheral nervous system. However, several noncontrolled studies have suggested concomitant inflammatory CNS demyelination similar to multiple sclerosis. The aim of this study was to investigate an involvement of the visual pathway in patients with CIDP.MethodsIn this prospective cross-sectional study, we used high-resolution spectral-domain optical coherence tomography to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…APOSTEL reporting recommendations were applied for SD-OCT methodology and results 13 . The methods are well-established and have also been used and described elsewhere 14 16 . For macular volume scans, 61 vertical scans centered on the fovea (30° × 25°, high-speed scanning mode) were captured.…”
Section: Methodsmentioning
confidence: 99%
“…APOSTEL reporting recommendations were applied for SD-OCT methodology and results 13 . The methods are well-established and have also been used and described elsewhere 14 16 . For macular volume scans, 61 vertical scans centered on the fovea (30° × 25°, high-speed scanning mode) were captured.…”
Section: Methodsmentioning
confidence: 99%
“…Visual evoked potential studies have revealed electrophysiologic evidence of subclinical optic nerve dysfunction in those with longstanding CIDP (2,4). A recent optical coherence tomography study found subtle retinal ganglion cell/inner plexiform layer neurodegeneration in patients with CIDP compared with healthy controls (18). The precise mechanism of optic nerve dysfunction in CIDP remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, signs of central nervous system (CNS) affection, such as fatigue, 3 cognitive 4 and visual abnormalities, 5 , 6 were reported to accompany typical sensorimotor CIDP symptoms. In this regard, it is notable that optical coherence tomography showed reduced volumes of the retinal ganglion cell (RGC) layer in patients with CIDP.…”
Section: Introductionmentioning
confidence: 99%